Confounders of severe asthma: diagnoses to consider when asthma symptoms persist despite optimal therapy - Alina Gherasim (World Allergy Organization Journal, 2018)
Abstract Asthma can often be challenging to diagnose especially when patients present with atypical symptoms. Therefore, it is important to have a broad differential diagnosis for asthma to ensure that other conditions are not missed. Clinicians must maintain a high index of suspicion for asthma mimickers, especially when patients fail to respond to conventional therapy. The purpose of this review is to briefly review some of the more common causes of asthma mimickers that clinicians should consider when the diagnosis of asthma is unclear.